An autonomous industrial robot for loading and unloading goods - Jaber Al Rashid; Kadir, Md. Abdul; Chowdhury, Md. Belayet (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.